ASUHAN KEBIDANAN PADA IBU HAMIL ANEMIA DENGAN PEMBERIAN BAYAM DAN MADU UNTUK MENINGKATKAN KADAR HEMOGLOBIN - Helen Kristeti; Silvia Mona (Universitas Batam, 2023)
WHO states the prevalence of anemia in various regions of the world is around 40-88%. In 2018 the prevalence of anemia, meanwhile in 2018 it increased to 48.9%. One alternative to meeting iron needs can be done by consuming green vegetables, one of which is spinach, combined with honey, because honey helps the formation of blood. Research objective Provide midwifery care to mildly anemic pregnant women by administering spinach and honey to increase hemoglobin levels. The type of research used in the preparation of practice reports is descriptive research using the case study method. The research was conducted at the Tanjung Balai Karimun Health Center in January 2023. The subject used in this study was a third trimester pregnant woman with mild anemia. Midwifery care for pregnant women with mild anemia by administering spinach and honey has been carried out. After conducting the study to the case evaluation, there was no gap between theory and practice in the field. Based on the results of midwifery care, it was found that the consumption of spinach and honey can be an alternative treatment for mild anemia in pregnant women because it can help increase hemoglobin levels